A amplitude das matérias de defesa no incidente de desconsideração da personalidade jurídica - Santos, Júlio César Guzzi dos (2019)
The theory of disregarding legal personality, especially with the Civil Procedure Code/2015, which aimed at filling a procedural gap that existed until then, is intriguing, because although the initial vision in conferring legal certainty, prestige principally constitutional principles, such as that of the adversary and of the ample defense, the procedural document lacks prediction regarding the matters of defense, specifically in the incident, that could be raised by the third one that is intended to reach with the disregard of the legal personality. It is sought to examine in this work if it can be achieved with the disregard of the personality, in the incident, taking into account, including, the fundamental procedural norms, to question in defense matters, besides its responsibility, the very merit of main action, deducting any and all grounds relating to the non-existence, invalidity or ineffectiveness of the debt